A transient lanthanum phosphinidene complex. Issue 98 (25th November 2020) - Watt, Fabian A.; McCabe, Karl N.; Schoch, Roland; Maron, Laurent; Hohloch, Stephan
Abstract : Deprotonation of the terminal phosphido complex (PN)2 La(PHMes) results in the C–H-activation of one of the PN ligands via a transient phosphinidene complex. Abstract : Deprotonation of the terminal phosphido complex (PN)2 La(PHMes) (1 ) results in the C–H-activation of one of the PN ligands, formally retaining the PHMes group. The reaction mechanism and the possible involvement of the transient phosphinidene complex 2 are investigated by theoretical and chemical means including a deuteration experiment employing (PN)2 La(PDMes) (1- d ). Furthermore, the thermal stability of product [K(2.2.2-cryptand)][(PN)(PNcyclo )La(PHMes)] (3b ) is examined, giving the diphosphido complex [K(2.2.2-cryptand)][(PN)2 La(P2 Mes2 )] (6 ).